2018
DOI: 10.3390/nano9010031
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite-Supported Gold Nanostars for the Uptake and SERS Detection of Tetracycline

Abstract: Magnetite nanoparticles (MNPs) decorated with gold nanostars (AuNSs) have been prepared by using a seed growth method without the addition of surfactants or colloidal stabilizers. The hybrid nanomaterials were investigated as adsorbents for the uptake of tetracycline (TC) from aqueous solutions and subsequent detection using surface-enhanced Raman scattering (SERS). Several parameters were investigated in order to optimize the performance of these hybrid platforms on the uptake and SERS detection of TC, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…389, 845 and 1035 cm –1 ) along with the enhancement of the Raman band at 1376 cm –1 . Previous reports have suggested that the enhancement of the band at 1376 cm –1 is due to the proximity of the methyl CH 3 and CN groups (Table ) to the surface of metal nanoparticles Note that a detection limit of 10 n m in thiram was achieved by considering this Raman feature as a diagnosis band (1376 cm –1 ). Although for this analyte concentration the band has low intensity, it was assessed as distinct from the background noise.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…389, 845 and 1035 cm –1 ) along with the enhancement of the Raman band at 1376 cm –1 . Previous reports have suggested that the enhancement of the band at 1376 cm –1 is due to the proximity of the methyl CH 3 and CN groups (Table ) to the surface of metal nanoparticles Note that a detection limit of 10 n m in thiram was achieved by considering this Raman feature as a diagnosis band (1376 cm –1 ). Although for this analyte concentration the band has low intensity, it was assessed as distinct from the background noise.…”
Section: Resultsmentioning
confidence: 95%
“…Several differences are noticeable by comparing the conventional Raman spectrum of thiram with the corresponding SERS spectrum. These differences arise mostly because in the SERS spectrum the spectroscopic fingerprints result from thiram adsorbed on the Au surfaces . The most pronounced difference is the absence of certain vibrational bands (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our interest in this field, prompted us to develop magnetic nanosorbents for SERS detection of TC. A first attempt involved the use of Fe 3 O 4 decorated with star shaped colloidal Au NPs 40 . While these systems have shown great potential in terms of SERS detection, the results also indicated the need for improvements mainly concerning the long term colloidal stability that allows adsorption studies for this analyte.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of antibiotics in humans, animals and aquaculture results in vast residuals in aquatic environments. 1,2 The persistence of antibiotic residues may cause a series of problems in ecosystems and public health because of the poor biodegradability of antibiotics. 3 Therefore, the removal of antibiotic residues in aquatic environments is of great concern in environmental protection.…”
Section: Introductionmentioning
confidence: 99%